PENGEMBANGAN MODEL PEMBELAJARAN PROGRAM KURSUS WIRAUSAHA PEDESAAN BERBASIS POTENSI LOKAL UNTUK KEMANDIRIAN WARGA BELAJAR - Thamrin A Kum (Publik : (Jurnal Ilmu Administrasi), 2015)
This research aimed to find out the learning model entrepreneurship rural course based on local potential program for independent residents of learn, using research and development method. Collection the data was conducted with interview, observation, documentation and the data analyzed with descriptive quantitative. The research found this data the PKBM administrators, the course administrators, the tutors, and the residents of learn were positively appreciated the experimented model. The andragogy approach, participative method, and individual guidance were successful in creating conducive learning atmosphere, giving opportunities for the residents of learn to actively participate and grow up the entrepreneurship motivation with exploiting the local potentials among the residents of learn. Based on the statistical test, this learning model influenced significantly towards the residents of learning results.